Future Foreign Financing - Mendershausen, Horst (The Review of Economics and Statistics, 1949)
The advancing recovery of European production and the apparent termination of the postwar boom in this country invite a new determination, of the objectives and magnitude of our foreign financing. We are rapidly moving into a new phase in which general shortfalls of production, compared with prewar, no longer represent the pressing problems to which our economic assistance must address itself. At least this is the case for the Western part of the world. Instead we are facing again the tensions between population growth and productivity particularly in the field of food in underdeveloped countries, and between the productive capacities of the developed industrial countries and the effective demand for their products. Insufficiency, instability, and unequal distribution of income in the world community threaten to limit and frustrate the postwar recovery.2 A broad and sustained economic expansion process on a world scale seems indicated to gear together existing productive capacities with existing but ineffective demands and to create new productive capacities that may provide more tolerable living standards for the people of the underdeveloped countries. As the leading and most productive nation of the world, the United States carries the major responsibility for the launching and direction of the expansion process. Such a process offers a way to satisfying simultaneously basic economic and political interests at home and abroad, our ability to supply investment and basic consumption goods and the needs for these abroad, our capacity to sustain a sizable export surplus and the need for a sizable import surplus in countries that want to develop their economies without resort to continual inflation, totalitarian politics, or civil war. It is the necessary basis for further progress in international cooperation and in the common management practices economic, political, military that have developed under our leadership in the war and postwar periods. The recovery process of the Western European nations, which has gone rather well so far in the field of production and inflation control particularly in Great Britain is beginnning to be marred by the lack of a longerrun policy of economic expansion. The expectation is spreading abroad that between now and I952 American foreign financing through existing channels will fall off without new channels being opened. The prospect of the termination of ECA without creation of a new and reliable stream of foreign financing adapted to the needs of the time invites retreats to economic isolationism, neglect of a balanced development of dependencies, and a destructive mania of saving dollars by cutting essential imports from America. The prospect discourages coordination of national investment policies and fosters economic warfare about limited markets between nations whose survival depends on persistent efforts to achieve a common management of their economic affairs. While economic cooperation in recovery necessarily must come to an end, uncertainty and confusion about its sequel make it appear that economic cooperation as such on the European continent, across the channel, and across the Atlantic is approaching its end. There arises a great problem of leadership for the United States, to renew the common venture and to define a fresh purpose.3 The